HIV KNOWLEDGE AND SEXUAL RELATIONSHIP NEGOTIATION AMONG INDONESIAN WOMEN LIVING IN AREAS WITH HIGH VS LOW HIV PREVALENCE - Sitohang, Marya Yenita; Arifa, Riza Fatma (Universitas Airlangga, 2024)
The prevalence of HIV in Indonesia is increasing, particularly among certain regions and married women. Such disparities have a significant impact on regional development. Knowledge of HIV and the ability to negotiate sexual relationships with their spouses can help prevent the spread of HIV in the population. This study aims to compare the HIV knowledge, stigma, sexual relationship negotiation, and attitudes toward negotiating safer sexual relationships of Indonesian married women in high and low HIV prevalence areas (Papua and West Sulawesi). Percentages, t-tests, and logistic regression were conducted using the 2017 Indonesian Demographic and Health Survey (IDHS) to analyze the differences between the two regions. The study found that HIV knowledge and negotiating skills differed between the two regions. Married women in the region with the highest HIV prevalence had better HIV knowledge but lower ability to negotiate sexual relationships with their husbands compared to married women living in the lowest HIV prevalence. The differences in HIV knowledge and ability to negotiate sexual relationships may be linked to gender disparities as well as efforts to prevent HIV transmission in the regions. Further studies are needed to explore the experiences and perspectives of married women in negotiating sexual relationships to develop more effective strategies to prevent HIV transmission in this population group.